Musaliyat Algharib In every strange thing from the point of view of modern history: An attempt to uncover and civilizational dialogue - Al-Qaisi, Mahmoud Abdul Wahid Mahmoud; Ahmed, Mawahib Adnan (Al-Adab Journal, 2020)
The paper is an attempt to understand the civilization's dialogue between Islam and Christianity through the travel of Imam Abdulrahman Al-Baghdadi,"Musalyat Algharib fi kuliamren 'Ajib"at the late 19th century, which represented the impact of Ottoman civilization on the South America. The travel was an important source on the beginning of the Brazilian society and the Islamic influence.